Rediscovering perifollicular elastolysis: A hitherto undocumented entity in India - Shyam B Verma; Gopinath Nandkumari (Wolters Kluwer Medknow Publications, 2015)
Perifollicular elastolysis, also known as papular acne scars is a common but taken for granted entity. It appears as asymptomatic whitish yellow papules on the trunk and proximal arms. Histologically there is loss of elastin around the pilosebaceous follicles. The lesions are the result of a scarring process that appear as papules and are often mistaken for papules of acne and are treated. A knowledge of this entity which has never been described before in India is being reiterated.